PENINGKATAN KAPASITAS LEGAL DRAFTING PEMERINTAHAN MELALUI PENYUSUNAN PERATURAN NAGARI DI SUMANIAK KECAMATAN SALIMPAUNG KABUPATEN TANAH DATAR - Ade Suzana Eka Putri; Hengki Andora; Jendrius Jendrius; Masrizal Masrizal (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
Nagari Sumaniak has so much potential in various aspects that it can be developed. This potential has been utilized well, but there is still some potential that has not been fully utilized. In the aspect of governance, it was identified that the Sumaniak government had difficulties in drafting nagari regulations due to the lack of information obtained by the nagari governments related to the preparation of nagari regulations. Meanwhile, the readiness of human resources (governments) is needed as actors in the regions in carrying out government affairs. For this reason, it is necessary to increase the capacity of the nagari governments in drafting nagari regulations through legal drafting training for the nagari governments. The aim of this activity is to increase the understanding and ability of the nagari governments through drafting regulations in the nagari. The activity was carried out in 2020-2021 at Nagari Sumaniak. The target of this activity is the entire Nagari government in Sumaniak. The method used in this activity is the PRA (Participatory Rural Appraisal) method to prepare a CAP (Community Action Plan). Activities are carried out through various stages, such as FGD / brainstorming with nagari governments, revision and drafting of nagari regulations, as well as training related to legal drafting for nagari governments. From the various activities that have been carried out, it can be seen that there is motivation throughout the nagari governments to make a real contribution in providing ideas and support in the preparation of the nagari. Then, increase the capacity of the nagari governments in preparing the nagari after the training. All resources are committed to being able to assist in the development of the nagari. It is recommended for the nagari government to always carry out regular training and improve its quality and capacity in carrying out work professionally. Then, it is hoped that the local governments can provide further understanding to the community, especially regarding the nagari governments in making a nagari regulations.